2006
DOI: 10.1111/j.1399-6576.2006.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two different hydroxyethyl starch solutions (HES200/0.5 vs. HES130/0.4) on the expression of platelet membrane glycoprotein

Abstract: This study showed that both HES200/0.5 and HES130/0.4 can inhibit platelet coagulation. Platelet dysfunction experienced a faster recovery after the infusion of HES130/0.4 than after HES200/0.5. Liquid resuscitation with HES130/0.4 may decrease the risk of hemorrhage in the operative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Nevertheless, HES 130 produced a not clinically significant platelet alteration. Similar results were reported for minor elective surgery [62].…”
Section: Clinical Evidencesupporting
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, HES 130 produced a not clinically significant platelet alteration. Similar results were reported for minor elective surgery [62].…”
Section: Clinical Evidencesupporting
confidence: 90%
“…In a retrospective study on transplanted kidneys from brain-dead donors, Legendre et al [66] found an 80% rate of renal injury after the infusion of HES 200/0 [62]. However, these anatomic alterations did not cause adverse effects in kidney transplant recipients.…”
Section: Clinical Evidencementioning
confidence: 97%
See 1 more Smart Citation
“…Blood loss and transfusion requirements are significantly reduced in major surgery when HES 130 is administered compared to HES 200 [21,22]. Furthermore, platelet dysfunction exhibits a faster recovery after the infusion of HES 130 compared to HES 200 [23]. However, little is known about the effects of the two different HES solutions on oxidative stress and the inflammatory response following HS/R.…”
Section: Discussionmentioning
confidence: 99%
“…While 10 mL/kg HES 130/0.4 had no platelet inhibiting effects, 37 20 mL/kg inhibited the expression of platelet membrane GP Ib‐IX (CD42b), GP IIb‐IIIa (CD41/61) and P‐selectin (CD62P) on ADP‐stimulated platelets 41 . Platelet function recovered within 6 hours after infusions of HES 130/0.4 but not after HES 200/0.5 41 …”
Section: Decrease In Platelet Functionmentioning
confidence: 99%